Feasibility of using natural SCMs in concrete for infrastructure applications. (30th November 2016) - Ghafari, Ehsan; Feys, Dimitri; Khayat, Kamal
Highlights: The feasibility of adding natural supplementary cementitious materials (SCMs) was evaluated. Perlite was found to be the suitable to enhance fresh properties. Pumice showed similar properties to the reference mixture in terms of fresh/hardened properties. The zeolite performed well in the hardened state, but showed inferior workability retention. Abstract: Nowadays concerns about the future availability of fly ash have arisen due to the implantation of pollution control devices in coal combustion plants and increased blending of powder river basin coals, both of which can influence the composition (and hence quality) of the resulting fly ash. An experimental study was conducted to evaluate the feasibility of incorporating natural supplementary cementitious materials (SCMs) mainly perlite, pumice, and zeolite in civil infrastructure applications. The influence of selected natural SCMs, on the hydration behavior, key fresh and hardened properties of cement paste and concrete mixtures was compared to mixtures without any SCM and with fly ash. The results indicated that Perlite may be the suitable material regarding fresh properties, but low pozzolanic reactivity and a reduction in compressive strength and modulus of elasticity may reduce its implementation for structural applications. Mixtures with 15 wt% pumice was shown to have similar properties to the reference mixture without fly ash, but had increased SP demand and low workability retention, making them more suitable for precast applications compared to ready-mix concrete. The zeolite performed very well in the hardened state, but had high admixture demand and inferior workability retention. From this study, it can be concluded that each of the three investigated alternatives SCMs that may be used to replace class C fly ash in concrete infrastructure applications.